Inovasi Media Pembelajaran Ular Tangga Untuk Meningkatkan Kemampuan Literasi Digital Pada Pembelajaran IPS Di SMP Negeri 2 Sawang Kabupaten Aceh Utara - Asvia Syura; Sumanti Sumanti; Cut Khairani (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to produce an innovative learning media in the form of a snakes and ladders game specifically designed to improve students' digital literacy in social studies learning at SMP Negeri 2 Sawang, North Aceh Regency. The research method used is research and development (R&D) with the DDDE development model which includes four main stages, namely Decide, Design, Development, and Evaluation. Data collection techniques in this study were carried out through interviews to explore initial needs and questionnaires to measure the level of media feasibility and student responses. The data analysis technique used is qualitative descriptive analysis to process data in the form of suggestions and input from experts, as well as quantitative descriptive analysis to process numerical data from the results of questionnaires and evaluations of students' digital literacy. The use of this snakes and ladders game media has been tested on 32 students at SMP Negeri 2 Sawang. The results of the study according to expert validation showed that the developed media obtained a score of 95% with very feasible criteria, and material expert validation showed that the quality of learning materials in the media obtained a score of 95% with very feasible criteria. In the small group trial phase, a score of 43.375 was obtained, while the student response questionnaire assessment showed a percentage of 89.5% with a very feasible criteria. The results of the effectiveness test for improving students' digital literacy showed a mean value of 0.7421, which is included in the effective category. Based on the assessments carried out by experts and students and the results of the effectiveness test, this snakes and ladders game media innovation is declared feasible and effective for use in social studies learning at SMP Negeri 2 Sawang.